2017
DOI: 10.24099/vet.arhiv.170208
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hepatitis E virus (HEV) presence in naturally infected seropositive domestic pigs and wild boars - an indication of wild boars having an important role in HEV epidemiology

Abstract: hepatitis e (he) is an emerging public health problem in developed countries worldwide. Nowadays, it is known that the hepatitis e virus (heV) has zoonotic potential, whereas domestic pigs and wild boars are recognized as the true reservoirs of the disease. Therefore, the aim of our study was to define the seroprevalence and viral persistence of heV in pigs and wild boars in Croatia. In total, 1424 samples originating from domestic pigs from 14 counties, and 1000 samples of wild boar origin, collected from 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…A lower seroprevalence of 32.94% was detected in swine in Croatia [11] and 40% in Bulgaria [12] but very similar seroprevalence (58.1%), as in our investigation, was demonstrated in Switzerland [25]. On the other hand, higher seroprevalence of 80% was established in fattening pigs in northern Greece [26].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A lower seroprevalence of 32.94% was detected in swine in Croatia [11] and 40% in Bulgaria [12] but very similar seroprevalence (58.1%), as in our investigation, was demonstrated in Switzerland [25]. On the other hand, higher seroprevalence of 80% was established in fattening pigs in northern Greece [26].…”
Section: Discussionsupporting
confidence: 84%
“…HEV infection is highly prevalent among the domestic pigs in Europe. Jemeršić et al [11] reported that the overall seroprevalence in Croatia was 32.94%. In Bulgaria, the total seroprevalence of HEV in pigs 1 to 6 months of age was 40%, being in piglets 50% and in fattening pigs 29.2% [12].…”
Section: Introductionmentioning
confidence: 99%
“…Zele et al reported HEV seroprevalence 30.21% (87/288) of wild boar serum samples from Slovenia [18]. Jemersic et al found 31.10% (311/1000; 95% CI: 28.31-34.04) HEV-positive wild boars in 6 of the 16 counties of Croatia [19]. Moderate and high HEV seropositivity among domestic pigs was observed in Southeastern Europe [20].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the overall HEV seroprevalence was shown to be 32.94% (range 8.33%-60.00%) in domestic pigs from 11 counties and 31.10% (range 7.70%-50.60%) in wild boars from six Croatian counties. While no positive HEV RNA samples were detected in domestic pigs, 11.33% seropositive wild boars were found to be HEV RNA positive indicating that wild boars may have a key role in HEV epidemiology[41].…”
Section: Croatiamentioning
confidence: 99%